Letter - Coomber, A. F.
041-0156-001 FULHAM CENTRAL LABOUR PARTY (Affiliated to National and London Labour Parties.) CENTRAL OFFICE: 131, DAWES ROAD. S.W.6 'PHONE: FULham 6371. VICE-PRESIDENTS: P.J. BARTON, H. PERRY. PRESIDENT: C. LANCASTER. HON. SEC. & TREASURER: A. F. COOMBER, 62, Hazlebury Road, Fulham, S.W.6 Sept 10th 1936 The Secretary Labour Party Transport Hse Dear Comrade, Enclosed please find cheque for £20.0.0 being the amount of collection of meeting held at Fulham Town Hall on 7th inst. for Spanish Workers Medical Unit. A receipt in due course will oblige. Yours fraternally, A.F. Coomber 12 SEP. 1936 292/946/41/156